ІMPROVEMENT OF THE METHOD OF QUALITY CONTROL OF THE ADSORBENT FOR HYDROGEN PURIFICATION OF A NUCLEAR POWER PLANT TURBINE GENERATOR - ZAITSEV, SERHII; KISHNEVSKY, VICTOR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article presents the results of improving the method of quality control of an adsorbent for hydrogen purification of a NPP turbine generator. The aim of the work is to improve the reliability of adsorbents in hydrogen purification filters in an oil-filled hydrogen-cooled NPP turbine generator by controlling the quality of carbon fibre adsorbents (CFM) during the determination of their aerodynamic resistance in the hydrogen flow and the adsorption of a standardised substance (benzene vapour) by CFM adsorbents in the hydrogen flow. Object of research: methods of quality control of the adsorbent for hydrogen purification of a hydrogen-cooled turbine generator in the structure of a nuclear power plant. Subjects of research: industrial CFM of UUT-2, ANM, AMT, URAL-T-5 brands. The following results were obtained: the structural diagram of the installation for determining the values of aerodynamic resistance of adsorbents at different linear velocities of hydrogen at the inlet to the studied adsorbents of the CFM type was improved; the values of aerodynamic resistance of CFM  layers at different numbers of their layers and linear velocities of hydrogen at the inlet to the studied CFM were determined; the adsorption of benzene vapours by CFM type adsorbents in a hydrogen stream at different concentrations of benzene vapours was investigated; recommendations for the placement of purification filters in hydrogen streams in a hydrogen-cooled turbine generator were developed. The results obtained can be used to improve the elements of the system for diagnosing the quality of adsorbent for hydrogen purification of a hydrogen-cooled turbine generator in the structure of a nuclear power plant.
Keywords: carbon fibre material; hydrogen; adsorption; turbine generator; aerodynamic drag; pyrolysis